К морфологии зубной коронки высших песчанок (Mammalia, Gerbillinae) - Павлинов, И.Я. (Вестник зоологии, 1979)
The corona of the first and the second cheek teeth of young specimen in the Meriones, Rhombomys, Psammomys genera and the corona of the upper third cheek teeth in the Rhombomys genus are represented by nonfused laminas. Long axes of laminas and a tooth often form an acute angle and the points of the laminas confluence are displaced externally. It permits supposing that arrangement of apexes in turns is initial for the corona of Gerbillinae.